Acceleration for proximal stochastic dual coordinate ascent algorithm in solving regularised loss minimisation with ℓ2 norm. Issue 5 (1st March 2018) - Tan, Beibei; Liu, Benyong
Abstract : An accelerated version of the proximal stochastic dual coordinate ascent (SDCA) algorithm in solving regularised loss minimisation with ℓ 2 norm is presented, wherein a momentum is introduced and the strong theoretical guarantees of SDCA are shared. Moreover, it is also suitable for various key machine learning optimisation problems including support vector machine (SVM), multiclass SVM, logistic regression, and ridge regression. In particular, the Nestrov's estimate sequence technique to adjust the weight coefficient dynamically and conveniently is adopted. It is applied for training linear SVM from the large training dataset. Experimental results show that the proposed method has a competitive classification performance and faster convergence speed than state‐of‐the‐art algorithms.